2021
DOI: 10.1007/s11030-021-10244-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the active compounds and mechanism of HuaShi XuanFei formula for prevention and treatment of COVID-19 based on network pharmacology and molecular docking analysis

Abstract: Graphic abstract Traditional Chinese medicine (TCM) has exerted positive effects in controlling the COVID-19 pandemic. HuaShi XuanFei Formula (HSXFF) was developed to treat patients with mild and general COVID-19 in Zhejiang Province, China. The present study seeks to explore its potentially active compounds and pharmacological mechanisms against COVID-19 based on network pharmacology, molecular docking, and molecular dynamics (MD) simulation. All components of HSXFF were harvested from the pharmaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 69 publications
(72 reference statements)
1
20
0
Order By: Relevance
“…Furthermore, this TF is associated with some human inflammatory diseases such as RA (417). In agreement with us, this TF was identified as a hub gene in several network-based COVID-19 studies (347,(418)(419)(420)(421). Therefore, this TF may have an immunoregulatory role during SARS-CoV-2 infection and be a potential therapeutic target.…”
Section: Turquoise Modulesupporting
confidence: 76%
“…Furthermore, this TF is associated with some human inflammatory diseases such as RA (417). In agreement with us, this TF was identified as a hub gene in several network-based COVID-19 studies (347,(418)(419)(420)(421). Therefore, this TF may have an immunoregulatory role during SARS-CoV-2 infection and be a potential therapeutic target.…”
Section: Turquoise Modulesupporting
confidence: 76%
“…In this study, the majority of participants reported the same purpose before (69.7%) / after (71.8%) the epidemic of COVID-19, as immune system has a close interaction with COVID-19 infection and cancer progression [22,23]. CAM was quite famous for its regulating immune system effect in cancer patients and fighting against COVID-19 [24,25], and cancer patients seemed to show more interest (70.2%) and confidence (79.4%) in CAM treatment during the COVID-19 though their frequency of CAM clinic visit dropped significantly.…”
Section: Discussionmentioning
confidence: 67%
“…In addition, other classes of compounds detected in GBB leaves, show high medicinal potential, such as the substance procyanidin B1, which can suppress the replication of the virus that causes hepatitis C, besides being a potential candidate molecule against coronaviruses, including COVID-19 [23][24][25]. Furthermore, the phenolic constituents present in GBB leaves are possibly responsible for the indirect prebiotic action, highlighting their benefit in the consumption of this plant, which is often neglected [26].…”
Section: Resultsmentioning
confidence: 99%